The ferromagnetic [Ln2Co6] heterometallic complexes. Issue 7 (27th January 2017) - Zhao, Xiao-Qing; Wang, Jin; Bao, Dong-Xu; Xiang, Shuo; Liu, Ya-Jun; Li, Yun-Chun
Abstract : Four 3d–4f [Ln2 Co6 ] complexes were fabricated. [Dy2 Co6 ] (1 ) and [Ho2 Co6 ] (2 ) displayed ferromagnetic coupling, and [Dy2 Co6 ] (1 ) exhibited slow magnetic relaxation. Abstract : Four 3d–4f heterometallic complexes with the formula, [Ln2 Co6 (OH)4 (L1 )6 (L2 )8 (CH3 CN)2 ]· n CH2 Cl2 (Ln = Dy (1 ), n = 0.5; Ho (2 ), n = 1; Gd (3 ), n = 1; Y (4 ), n = 1; HL1 = 6-chloro-2-pyridinol, HL2 = pivalic acid), were synthesized. Single-crystal X-ray diffraction analyses revealed that complexes1–4 consisted of a [Ln2 Co6 ] core, featuring a Ln–Ln edge-sharing double-trigonal-bipyramid configuration. The magnetic susceptibilities revealed ferromagnetic coupling within complexes1 and2, and complex1 displayed slow relaxation of magnetization.